Rethinking Grammar in Language Arts: Insights from an Australian Survey of Teachers' Subject Knowledge - Macken-Horarik, Mary; Love, Kristina; Horarik, Stefan (Research in the teaching of English, 2018)
In English-speaking countries such as the United States, the United Kingdom, Australia, and New Zealand, there is a renewed focus on teaching about language in school curricula and evidence of a paradigm shift in approaches to grammar instruction. Calls for contextualized, meaning-based, even multisemiotic grammars are emerging in several countries. In Australia, the motivation for teachers to expand grammatical expertise has been sharpened by the introduction of the Australian Curriculum: English, with its requirement to teach "the structures and functions of word and sentence-level grammar and text patterns and the connections between them" (National Curriculum Board, 2009, p. 7). This paper reports on an Australian survey that sought evidence of the profession's levels of understanding of, and confidence to teach, the relational view of language underpinning this curriculum. Drawing on quantitative and qualitative responses from 373 English teachers across all years of schooling, the survey provides a national snapshot of their views on what is important in knowledge about language (KAL), levels of confidence in implementing this knowledge and emerging disjunctions between avowed and actual KAL in the profession. We relate this disjunction to international research suggesting that teacher confidence outstrips actual KAL, and explore the possibility that teachers' overall expressions of confidence may hide uncertainty about the implications of a relational approach to grammar. The paper concludes with discussion of limitations and implications of our study for future research into teacher subject knowledge, especially grammar.